Synthesis and characterization of pH-sensitive acrylamide/acrylic acid hydrogels - Pinto, Virgínia (2011)
Different samples of pH-sensitive hydrogel particles were produced using inverse-suspension, leading to the identification of the influence on their end-use properties of the degree of neutralization of AA monomer and the initial composition of the terpolymerization system which are therefore the key parameters of the synthesis. These studies were also used to develop a kinetic model improving the design of production processes of tailored smart polymers.